Animal Diseases - Fu, Zhen F.; Chen, Huanchun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: BioMed Central.)
Animal Diseases focuses on the latest research and technology advances in animal diseases that are closely related to human health and explores challenges and countermeasures that environmental changes pose to animal and human. It provides rapid publication of the most innovative and quality papers that address the etiology and pathogenesis of infectious (viral, bacterial and parasitic) and non-infectious (genetic disorders, tumors, metabolic diseases etc.) diseases linked to animals, as well as the progresses towards their prevention and treatments, including, but not limited to, epidemiology, etiology, pathology, immunology, pathogenesis, diagnosis, prevention and treatments. Original research articles will be published in the following headings: Discovery of etiological agents for animal diseases Epidemiology of animal and zoonotic diseases Host tropism and transboundary spread of animal and zoonotic pathogens Pathogenesis and biology of new and re-emerging animal diseases Etiology of non-infectious diseases such as genetic, neoplastic and metabolic diseases Immunology and host-pathogen interactions Rational use and invention of veterinary drugs and novel therapeutics Drug resistance and drug residues Biomarker identification and novel diagnostic tools Vaccines and prevention strategies for animal diseases In addition, the journal publishes Editorials, Highlights, and Comments on current, significant events and topics in global animal disease fields with international interests.
Keywords: Veterinary medicine; Medicine, Preventive; Health promotion; Diseases; Genetics; Veterinary Science; Health Promotion and Disease Prevention; Diseases; Genetics and Genomics